The total cost for a single order of x cartridges can be represented by the algebraic expression:
Total Cost = 26x + 6.50
#3.
Printer ink cartridges cost $26 each. The company that sells the ink cartridges charges a flat rate of $6.50, no matter how many ink cartridges you buy.
Write an algebraic expression that describes the total cost for a single order of x, cartridges.
HINT: Use the table to help you write the expression.
Number of Cartridges
Total Cost
11 answers
Number of cartridges total cost
1. 26(1)+6.50
2
3
X
1. 26(1)+6.50
2
3
X
The total cost for a single order of x cartridges can be represented by the algebraic expression:
Total Cost = (26x) + 6.50
Total Cost = (26x) + 6.50
Number of cartridges total cost
1. 26(1)+6.50
2
3
X
Can you make this table
1. 26(1)+6.50
2
3
X
Can you make this table
Sure! Here is the table you requested:
Number of Cartridges | Total Cost
-------------------------------------
1 | 26(1) + 6.50
2 | 26(2) + 6.50
3 | 26(3) + 6.50
x | 26x + 6.50
Note: The total cost for each number of cartridges is calculated by multiplying the number of cartridges by the cost per cartridge ($26) and then adding the flat rate of $6.50.
Number of Cartridges | Total Cost
-------------------------------------
1 | 26(1) + 6.50
2 | 26(2) + 6.50
3 | 26(3) + 6.50
x | 26x + 6.50
Note: The total cost for each number of cartridges is calculated by multiplying the number of cartridges by the cost per cartridge ($26) and then adding the flat rate of $6.50.
Evaluate the expression 3b-ac when a=2,b=3 and c= -1.5
To evaluate the expression 3b - ac when a = 2, b = 3, and c = -1.5, we substitute the given values into the expression:
3b - ac = 3(3) - 2(2) - 1.5 = 9 - 4 - 1.5 = 3.5
3b - ac = 3(3) - 2(2) - 1.5 = 9 - 4 - 1.5 = 3.5
So what's the answer 12 -5 15.5 or 24
The answer is 3.5.
Evaluate the expression 3b-ac when a=2,b=3 and c= -1.5
12
-5
-15.5
24
12
-5
-15.5
24
To evaluate the expression 3b - ac when a = 2, b = 3, and c = -1.5, we substitute the given values into the expression:
3b - ac = 3(3) - 2(-1.5) = 9 - (-3) = 9 + 3 = 12
Therefore, the answer is 12.
3b - ac = 3(3) - 2(-1.5) = 9 - (-3) = 9 + 3 = 12
Therefore, the answer is 12.